2014
DOI: 10.1097/mlr.0000000000000213
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Surgery Centers and Outpatient Procedure Use Among Medicare Beneficiaries

Abstract: Background There has been a strong push to move outpatient surgery from hospital settings to ambulatory surgery centers (ASCs). Despite the efficiency advantages of ASCs, many are concerned that these facilities could increase overall utilization. Objective To assess the impact of ASC opening on rates of outpatient surgery. Design A retrospective cohort study of Medicare beneficiaries undergoing outpatient surgery between 2001 and 2010. We compared population-based rates of outpatient surgery in Hospital S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 15 publications
1
57
0
Order By: Relevance
“…19 A recent trend has been early discharge of patients from hospital after surgical procedures, transitioning towards a more outpatient-based surgical paradigm. [20][21][22] Indeed, early hospital discharge for cancer patients expedites chemotherapy and/or radiotherapy and also potentially improves patient outcomes by decreasing the time period between surgery and resumption of daily activities. This trend towards early discharge has been somewhat resisted by many in the field of intracranial tumour surgery.…”
Section: Discussionmentioning
confidence: 99%
“…19 A recent trend has been early discharge of patients from hospital after surgical procedures, transitioning towards a more outpatient-based surgical paradigm. [20][21][22] Indeed, early hospital discharge for cancer patients expedites chemotherapy and/or radiotherapy and also potentially improves patient outcomes by decreasing the time period between surgery and resumption of daily activities. This trend towards early discharge has been somewhat resisted by many in the field of intracranial tumour surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of physicians included in the analysis were male (95.9% [n ÂĽ 5430]) and practiced in urban locations (92.6% [n ÂĽ 5243]; Table II). The median number of years in practice was 23 years (IQR, 16-30 years), and the median number of patients who received a new diagnosis of claudication during the study period was 22 (IQR, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Patient and physician characteristics associated with early PVI. Based on univariable logistic regression analysis, patient characteristics associated with higher early PVI rates included age 65 to 74 years, male sex, hypertension, and smoking (all P < .001; Table III).…”
Section: Resultsmentioning
confidence: 99%
“…24 This must be considered in the broader context of ASC utilization for Medicare beneficiaries. Hollenbeck et al 25 found that rather than redistributing patients from hospital settings to ASCs, outpatient surgery rates in areas where ASCs were opened increased by 10.9% between 2001 and 2010, which was significantly higher than the 2.4% increase where ASCs were already present and 0.6% increase in areas where ASCs were never present. In another study of Medicare claims for endovascular interventions, there was a 298% increase in atherectomy cases in the OBL setting from 2011 to 2014 compared with a 27% increase in the hospital outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…; Hollenbeck et al. ). Importantly, this growth appears to be driven by procedures with less stringent clinical indications for their use (Hollingsworth et al.…”
Section: Commentmentioning
confidence: 98%
“…Third, physician owners preferentially manage well-insured patients (Gabel et al 2008) and perform well-reimbursed procedures (Plotzke and Courtemanche 2011) at ASCs. Finally, the opening of an ASC in a health care market has been associated with significantly higher rates of outpatient surgery relative to markets without them (Hollingsworth et al 2011;Hollenbeck et al 2014). Importantly, this growth appears to be driven by procedures with less stringent clinical indications for their use (Hollingsworth et al 2011).…”
Section: Commentmentioning
confidence: 99%